2015
DOI: 10.1016/j.cell.2015.04.034
|View full text |Cite
|
Sign up to set email alerts
|

RNA Exosome-Regulated Long Non-Coding RNA Transcription Controls Super-Enhancer Activity

Abstract: We have ablated the cellular RNA degradation machinery in differentiated B cells and pluripotent embryonic stem (ES) cells by conditional mutagenesis of core (Exosc3) and nuclear RNase (Exosc10) components of RNA exosome and identified a vast number of long non-coding RNAs (lncRNAs) and enhancer RNAs (eRNAs) with emergent functionality. Unexpectedly, eRNA-expressing regions accumulate R-loop structures upon RNA exosome ablation, thus demonstrating the role of RNA exosome in resolving deleterious DNA/RNA hybrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
395
0
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 395 publications
(437 citation statements)
references
References 82 publications
17
395
0
3
Order By: Relevance
“…Although their levels are low, the 3′RR transcripts [3′RR enhancer RNAs (eRNAs)] can readily be detected upon stimulation of splenic B cells and correlate with the 3′RR activity in activated B cells (23,24). Additionally, recent work involved hs4 eRNA in long-range interactions with a far downstream nonIg sequence (25). Because the deletion of 5′hs1RI may have impacted the long-range interactions of the 3′RR and potentially altered its activity, it was important to check the effect of the mutation on the 3′RR eRNA levels.…”
Section: Significancementioning
confidence: 99%
“…Although their levels are low, the 3′RR transcripts [3′RR enhancer RNAs (eRNAs)] can readily be detected upon stimulation of splenic B cells and correlate with the 3′RR activity in activated B cells (23,24). Additionally, recent work involved hs4 eRNA in long-range interactions with a far downstream nonIg sequence (25). Because the deletion of 5′hs1RI may have impacted the long-range interactions of the 3′RR and potentially altered its activity, it was important to check the effect of the mutation on the 3′RR eRNA levels.…”
Section: Significancementioning
confidence: 99%
“…DRIP revealed that loss of DBP2 results in accumulation of lncRNA-dependent R-loops across all 3 GAL cluster genes, consistent with the length of the GAL10 antisense lncRNA and 3 0 extended GAL10s lncRNA. 58 Interestingly, the nuclear RNA decay enzyme RRP6 also controls R-loop formation in mammalian cells between eRNAs and enhancers, 73 indicating that RNP assembly and/or processing may dictate the function of numerous lncRNAs. Since simultaneous loss of DBP2 and RRP6 is lethal in yeast, indicating functional overlap, 58 it will be interesting to determine if orthologs of Dbp2 (DDX5 in mammals) also controls R-loop formation in multicellular eukaryotes.…”
mentioning
confidence: 99%
“…Due to not having a comprehensive knowledge of their function, LncRNAs are categorized based on their location relative to the protein‐coding genes as: sense (which are transcribed from sense strand of protein‐coding genes and overlap one or more exons and introns), antisense (which are transcribed from the antisense strand of protein‐coding genes), bidirectional (which are located 1 kb away from promoters of protein‐coding genes in the opposite direction), intronic (which are located between exons of protein‐coding genes) and intergenic (which are located between two protein‐coding genes) 5, 7, 14, 15. On the other hand, other lncRNAs including natural antisense transcripts (NATs) 16, circular RNAs (cRNAs) 17, 18, enhancer ncRNAs (eRNAs) 19, 20, 21, transcribed pseudogenes 22 and telomerase RNA component (TERC) 23 have been also identified.…”
Section: Introductionmentioning
confidence: 99%